Adam Watkins' 4th Grade Manchester-Gate Class Tour of Fresno Bee Facility at 1921 E Street, Fresno - Watkins, Howard::::::::: (1987)
Front row (L-R): Mark Poochogian, Corky Sellers, Jennifer Stover, Juan Carlos Montoy, Chip Henderson, Dong Nguyen, Estevan Bonilla, Jose Serrato, Heather Setrakian. Second row: Parent Phillip Setrakian, Kristi Peerson (over his shoulder), Raja Visweswaran, Brandon Fujita, Zoltan DeWitt, Janine Dirlam, Than Merrill, Jill Buresh Nail, Emily Hill. Third row: Larry Orender (in red shirt), Stacey Harter, Deidtra Montgomery, Victoria Lawson, Kristi Painter, Jenny Nelson, Adrienne Sievert, Adam Watkins. Back row: ?, Barbara Buresh,?, Nora Dewitt, Debbie Poochigian, Sandy Setrakian, Howard Watkins, ?, ?.